PENGARUH EFEKTIVITAS MANAJERIAL, SELF-EFFICACY, STRES KERJA DAN MOTIVASI KERJA TERHADAP KINERJA DOSEN KEBIDANAN DI PROVINSI LAMPUNG - Sudarmi . (Jurnal Manajemen., 2015)
The objective of this research is to explore the effect of managerialeffectiveness, self-efficacy, job stress and work motivation on the performance ofmidwifery lecturer in Lampung Province. This research used a quantitative surveymethod. The data was collected with questionnaires and analyzed using path analysistechnique. population of the research study midwifery lecturer of province Lampungtotaling 167 lecturer, sampled 118 respondents sampling technique with proportionalrandom sampling method.The results of this research: the managerial effectiveness of adirect positive effect on performance, self-efficacy of a direct positive effect onperformance, work stress of a direct negative effect on performance, work motivationof a direct positive effect on performance, managerial effectiveness direct negativeeffect on job stres, self-efficacy direct negative effect on job stress, managerialeffectiveness of direct positive effect on work motivation, self-efficacy positive directeffect on work motivation and work stress and negative direct effect on workmotivation